2024
DOI: 10.1186/s12944-023-01972-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel biomarkers based on lipid metabolism-related molecular subtypes for moderately severe and severe acute pancreatitis

Jifeng Liu,
Lei Zhong,
Yunshu Zhang
et al.

Abstract: Background Acute pancreatitis (AP) is an unpredictable and potentially fatal disorder. A derailed or unbalanced immune response may be the root of the disease’s severe course. Disorders of lipid metabolism are highly correlated with the occurrence and severity of AP. We aimed to characterize the contribution and immunological characteristics of lipid metabolism-related genes (LMRGs) in non-mild acute pancreatitis (NMAP) and identify a robust subtype and biomarker for NMAP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several studies have shown that many genes are associated with macrophages and CD8 T cells in the development of AP. 28,29 In our study, two diagnostic genes, arginase 1 (ARG1) and Vanin1 (VNN1), were obtained, and their expression was higher in the AP group than in the normal group. ARG1 is not only a marker of M2 macrophages, but also a metabolic enzyme mainly located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have shown that many genes are associated with macrophages and CD8 T cells in the development of AP. 28,29 In our study, two diagnostic genes, arginase 1 (ARG1) and Vanin1 (VNN1), were obtained, and their expression was higher in the AP group than in the normal group. ARG1 is not only a marker of M2 macrophages, but also a metabolic enzyme mainly located in the cytoplasm.…”
Section: Discussionmentioning
confidence: 74%
“…The primary mode of interaction between gut microbiota and the host is through metabolites; however, there remains a significant gap in understanding their respective roles within biological networks associated with AP. A high correlation exists between AP severity and lipid metabolism disorders 22 . The current investigation mainly examined the metabolism impact of Amuc_1098 in AP mice and explored the possible underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Host-microbiota interactions are primarily mediated by metabolites, but their roles in AP networks are poorly understood. Lipid metabolism disorders are highly correlated with AP occurrence and severity 22 . Akkermansia muciniphila has been shown to affect intestinal immunity, glucose metabolism, and lipid metabolism 23 .…”
Section: Introductionmentioning
confidence: 99%